Transcriptome immunomodulation of in-feed additives in Atlantic salmon Salmo salar infected with sea lice Caligus rogercresseyi. - Nuñez-Acuña, G.; Goncalves, A. T.; Valenzuela-Muñoz, V.; Pino-Marambio, J.; Wadsworth, S.; Gallardo-Escarate, C. (Fish & Shellfish Immunology, 2020)
One of the most significant threats to the Chilean salmon aquaculture industry is the ectoparasitic sea louse Caligus rogercresseyi. To cope with sea lice infestations, functional diets have become an important component in strengthening the host immune r FONDAP FONDAP